2020
DOI: 10.3390/agronomy10010127
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biochemical, Anatomical, Morphological, and Physiological Responses to Salinity Stress in Wheat and Barley Genotypes Deferring in Salinity Tolerance

Abstract: A greenhouse hydroponic experiment was performed using salt-tolerant (cv. Suntop) and -sensitive (Sunmate) wheat cultivars and a salt-tolerant barley cv. CM72 to evaluate how cultivar and species differ in response to salinity stress. Results showed that wheat cv. Suntop performed high tolerance to salinity, being similar tolerance to salinity with CM72, compared with cv. Sunmate. Similar to CM72, Suntop recorded less salinity induced increase in malondialdehyde (MDA) accumulation and less reduction in plant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
101
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(124 citation statements)
references
References 61 publications
23
101
0
Order By: Relevance
“…Studying barley, Han et al (2018) found tolerant genotypes to exhibit lower reductions in their dry biomass and less Na + accumulated in their roots and shoots than did the other wild or cultivated genotypes investigated. Consistent with our data, Zeeshan et al (2020) recently reported that the reduction in plant dry weight was much more noticeable in sensitive wheat cultivars subjected to salt stress. Similar results had also been reported by Kiani et al (2015) and Kumar et al (2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Studying barley, Han et al (2018) found tolerant genotypes to exhibit lower reductions in their dry biomass and less Na + accumulated in their roots and shoots than did the other wild or cultivated genotypes investigated. Consistent with our data, Zeeshan et al (2020) recently reported that the reduction in plant dry weight was much more noticeable in sensitive wheat cultivars subjected to salt stress. Similar results had also been reported by Kiani et al (2015) and Kumar et al (2017).…”
Section: Discussionsupporting
confidence: 93%
“…cylindrica genotypes (Kiani et al 2015) and salt-tolerant wheat cultivars (Kumar et al 2017). These findings are also complements to those reported on wheat and barley by Zeeshan et al (2020) who found that salt-stress induced significant changes in MDA content among their cultivars, with the highest recorded for a sensitive (Sunmate) wheat cultivar. MDA is one of the end products of lipid peroxidation indicating the status of ROS (reactive oxygen species).…”
Section: Discussionsupporting
confidence: 86%
“…On the contrary, the tolerant varieties limited lipid peroxidation during salinity stress. This enhancement of H 2 O 2 and TBARs content indicates the prevalence of oxidative stress, and this may be one of the possible mechanisms by which toxicity of salinity could be manifested in the plant tissues [ 33 , 34 ]. As a result, low H 2 O 2 content is strongly correlated with tolerance to salt-induced oxidative stress in wheat and barley [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suntop and barley cv. CM72, suggesting that Sunmate failed to some extent to restrict the accumulation of Na + in sensitive tissue like leaves or leaf canopy [17]. Besides, we also investigated plasma membrane Na + /H + antiporter, namely, SOS1, a long-distance Na + transport controller [41] that involves in transporting Na + into extracellular space after Na + enters the cell [42].…”
Section: Discussionmentioning
confidence: 99%